The Influence of Leadership and Work Environment on The Performance of Pagedangan Village Office Employees, Pagedangan District, Tangerang District - Irma Sari Octaviani; Didi Sunardi (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine the influence of Leadership and Work Environment on the Performance of Pagedangan Village Office Employees, Pagedangan District, Tangerang Regency. The method used in this study uses the associative method. The population in this study were all employees of the Pagedangan Village Office, Pagedangan District, Tangerang Regency. The number of samples used were 98 employees. Methods of data analysis using multiple linear regression. The results of this study indicate that there is a positive and significant influence between leadership partially on the performance of employees of the Pagedangan Village Office, Pagedangan District, Tangerang Regency. The work environment has a partially significant effect on the performance of employees of the Pagedangan Village Office, Pagedangan District, Tangerang Regency.